Initial results of ixekizumab efficacy and safety in real‐world plaque psoriasis patients: a multicentre retrospective study. (13th November 2018) - Deza, G.; Notario, J.; Lopez‐Ferrer, A.; Vilarrasa, E.; Ferran, M.; del Alcazar, E.; Carrascosa, J.M.; Corral, M.; Salleras, M.; Ribera, M.; Puig, L.; Pujol, R. M.; et al.
Abstract: Background: Ixekizumab (anti‐IL17A) is effective as treatment for moderate‐to‐severe plaque psoriasis, but real‐life data on effectiveness and safety are currently very limited. Objective: To evaluate the efficacy and safety of ixekizumab in a cohort of real‐life plaque psoriasis patients. Methods: Retrospective chart review of 100 patients with moderate‐to‐severe plaque psoriasis treated with ixekizumab at seven Spanish dermatological centres. Results: According to the as observed analysis, the percentage of patients achieving a 75% and 90% of reduction from the baseline score of Psoriasis Area and Severity Index (PASI) was 87.5%–50.0% at week 12–16; 88.3%–58.4% at week 24 and 82.9%–58.5% at week 52, respectively. The mean ± standard deviation (SD) score of PASI at baseline was 12.9 ± 9.2, and it declined rapidly after ixekizumab administration to 1.9 ± 4.0 ( P < 0.001) at week 12–16 and was maintained at 1.7 ± 4.1 and 1.8 ± 2.9 at week 24 and 52, respectively. Ixekizumab response was not affected by clinical variables like body mass index, disease duration or the presence of psoriatic arthritis. However, the bio‐naive group showed significantly higher PASI 75 response rate at week 12–16 compared to patients previously exposed to biologic agents ( P = 0.037). Twenty‐six (26%) patients experienced adverse events (AEs) during the follow‐up period, being most of them of mild‐to‐moderate intensity. The most common AE was local reaction at the site of injection (14/26; 53.8%). At the end of the observational period, 15 (15%) patients discontinued ixekizumab treatment due to limited clinical improvement ( n = 11), adverse events ( n = 3) or lost to follow‐up ( n = 1) within a mean ± SD time of 6.0 ± 3.9 months. Conclusion: The present study illustrates the initial experience with ixekizumab in real‐world clinical practice confirming its usefulness and safety in the management of plaque psoriasis patients.